Mesenchymal stem cell chondrogenesis: composite growth factor–bioreactor synergism for human stem cell chondrogenesis. (March 2013) - Petrou, Marios; Niemeyer, Philipp; Stoddart, Martin J; Grad, Sibylle; Bernstein, Anke; Mayr, Hermann O; Bode, Gerrit; Sudkamp, Norbert; Alini, Mauro; Salzmann, Gian M
Background: Effective mesenchymal stem cell chondrogenesis can be accomplished by using a tailored mechanical–biochemical stimulus. To achieve this requires parallel suppression of hypertrophy and osteogenesis.Materials & methods: We compared the effects of isolated bioreactor stimulation, isolated growth factor (TGF-β1 or IGF-1) application and their combined stimulation on human bone marrow-derived mesenchymal stem cells cultured within 3D scaffolds. Free-swelling cell-matrix constructs underwent identical growth factor stimulation for control.Results: Mechanical stimulation provoked stronger chondrogenic differentiation than free-swelling culture. Chondrogenesis by the addition of TGF-β1 was enhanced compared with single physical stimulation. There were no such effects under the influence of IGF-1 alone. Composite application of multiaxial mechanical stimulation plus TGF-β1 and IGF-1 not only triggered the strongest chondrogenesis overall, but also the strongest hypertrophy and osteogenesis.Conclusion: Bioreactor-induced chondrogenic differentiation of human mesenchymal stem cells can be effectively enhanced by growth factor addition, while the partially effective suppression of unwanted signs of endochondral ossification requires further scientific input.